alguem pode,resolver metodo,da,substituiçao
Anexos:
![](https://pt-static.z-dn.net/files/d1a/97f16b6a3c9eea1a414ee150befd1f21.jpg)
Soluções para a tarefa
Respondido por
1
SISTEMAS
MÉTODO SUBSTITUIÇÃO
x - 3y = - 7 ⇒ x = - 7 + 3y
3x + 2y = 12
3 ( - 7 + 3y ) + 2y = 12
- 21 + 9y + 2y = 12
11y = 12 + 21
11y = 33
y = 33/11
y = 3
x = - 7 + 3y
x = - 7 + 3(3)
x = - 7 + 9
x = 2
S = { 2 e 3 }
MÉTODO SUBSTITUIÇÃO
x - 3y = - 7 ⇒ x = - 7 + 3y
3x + 2y = 12
3 ( - 7 + 3y ) + 2y = 12
- 21 + 9y + 2y = 12
11y = 12 + 21
11y = 33
y = 33/11
y = 3
x = - 7 + 3y
x = - 7 + 3(3)
x = - 7 + 9
x = 2
S = { 2 e 3 }
silguicastro:
obrigada ,valeu !!!
Respondido por
1
Olá Silgui !
![\left \{ {{x - 3y = - 7} \atop {3x + 2y = 12 }} \right. \\ \\ \left \{ {{- 3x + 9y = 21} \atop {3x + 2y = 12}}\right. \\ \\ 11y = 33 \\ y = \frac{33}{11} \\ y = 3 \left \{ {{x - 3y = - 7} \atop {3x + 2y = 12 }} \right. \\ \\ \left \{ {{- 3x + 9y = 21} \atop {3x + 2y = 12}}\right. \\ \\ 11y = 33 \\ y = \frac{33}{11} \\ y = 3](https://tex.z-dn.net/?f=+%5Cleft+%5C%7B+%7B%7Bx+-+3y+%3D+-+7%7D+%5Catop+%7B3x+%2B+2y+%3D+12++%7D%7D+%5Cright.++%5C%5C++%5C%5C+++%5Cleft+%5C%7B+%7B%7B-+3x+%2B+9y+%3D+21%7D+%5Catop+%7B3x+%2B+2y+%3D+12%7D%7D%5Cright.++%5C%5C++%5C%5C+11y+%3D+33+%5C%5C+y+%3D++%5Cfrac%7B33%7D%7B11%7D++%5C%5C+y+%3D+3+)
![x - 3y = - 7 \\ x = - 7 + 3y \\ x = - 7 + 3 . ( 3 ) \\ x = - 7 + 9 \\ x = 2 x - 3y = - 7 \\ x = - 7 + 3y \\ x = - 7 + 3 . ( 3 ) \\ x = - 7 + 9 \\ x = 2](https://tex.z-dn.net/?f=x+-+3y+%3D+-+7++%5C%5C+x+%3D+-+7+%2B+3y+%5C%5C+x+%3D+-+7+%2B+3+.+%28+3+%29+%5C%5C+x+%3D+-+7+%2B+9+%5C%5C+x+%3D+2)
x y
S = { 3 , 2 }
Tenha bons estudos !
x y
S = { 3 , 2 }
Tenha bons estudos !
Perguntas interessantes